2010
DOI: 10.1002/ana.22210
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the future of stroke: II. Hemorrhage

Abstract: Bleeding into the brain or adjacent structures is one of the most devastating neurological conditions, incurring tremendous emotional, financial, and societal costs. Imaging is essential to differentiate variants of hemorrhage, as the clinical features may be insufficient. A comprehensive approach to hemorrhage therefore relies on imaging to disclose pathophysiology, elucidate mechanisms, and thereby open further avenues to effective treatment. Hemorrhage patterns from superficial to deep locations in the brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 104 publications
(108 reference statements)
0
8
0
Order By: Relevance
“…For example, perfusion imaging provides important information about the hemodynamics in terms of affected area and degree of perfusion abnormality. Chronic carotid artery occlusion has been shown to go ahead with minor changes of the perfusion dynamics as assessed with maps of time to peak or mean transit time while the cerebral blood volume is not decreased and there are no or minor apparent diffusion coefficient changes [146,147]. Conversely, severe decreases of cerebral blood volume in acute stroke predict secondary hemorrhage after systemic thrombolysis [148].…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…For example, perfusion imaging provides important information about the hemodynamics in terms of affected area and degree of perfusion abnormality. Chronic carotid artery occlusion has been shown to go ahead with minor changes of the perfusion dynamics as assessed with maps of time to peak or mean transit time while the cerebral blood volume is not decreased and there are no or minor apparent diffusion coefficient changes [146,147]. Conversely, severe decreases of cerebral blood volume in acute stroke predict secondary hemorrhage after systemic thrombolysis [148].…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Many other studies also reported a low rate of mortality and major disability in patients with posterior circulation strokes [18,19]. Possible collateral circulation [20] and relative high threshold to ischemic damage [21] might explain in part the relative resistance of posterior fossa tissue to ischemia. This explains the recent data showing that time window to open occlusions in the vertebrobasilar system might be longer than that in anterior circulation [22].…”
Section: Discussionmentioning
confidence: 91%
“…With imaging identification of this sign, it is important to note that several vascular and nonvascular mimics exist, which include but are not limited to central nervous system malignancy, resulting in intraparenchymal hemorrhage [18, 19]. The degree of extension of hemorrhage in itself may lie in the balance between intracranial pressure differentials, pressure differentials from adjacent tissue, and venous structures, as well as baseline condition of the surrounding white matter [20, 21]. …”
Section: Intracerebral Hemorrhagementioning
confidence: 99%
“…Using MRI imaging, Lou et al [26] demonstrateda correlation between iron content in the area of edema and the degree of perihematomal edema. MRI certainly adds to the assessment of prognosis in terms of offering additional insight into potential secondary neuronal injury resultant from initial hematoma [20]. …”
Section: Intracerebral Hemorrhagementioning
confidence: 99%
See 1 more Smart Citation